24th Digital Avionics Systems Conference
DOI: 10.1109/dasc.2005.1563307
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Flight Critical Data Over Internet Protocol

Abstract: Abstract. The aviation industry forms an important component of the nation's critical infrastructure. By considering the issues involved in protecting the operational aspects of the aviation industry, in conjunction with the introduction of Internet access within an airplane, the authors present the possibility of providing an additional path for the transport of critical content between and airplane and ground stations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…• some solutions do not consider the different "preferences" that could be expressed by multimedia applications, where some ones may wish to prioritize bandwidth [12] while others may prefer prioritize delay [9];…”
Section: Specific Transport Protocolsmentioning
confidence: 99%
“…• some solutions do not consider the different "preferences" that could be expressed by multimedia applications, where some ones may wish to prioritize bandwidth [12] while others may prefer prioritize delay [9];…”
Section: Specific Transport Protocolsmentioning
confidence: 99%
“…In [1] and [2], the authors have shown that the available IP connectivity between aircraft and ground can be used as a supplementary mechanism to aid communication and navigation from aircraft to ground. This connectivity is established with the help of satellite links and Mobile IP [3] and the concept can be extended to provide support for surveillance related information.…”
Section: Ip Connectivitymentioning
confidence: 99%